Distribution of microelements in the tissues and organs of saffron cod Eleginus gracilis (Tilesius, 1810) from the coastal waters of Sakhalin Island - Y. N. Poltev; T. G. Koreneva; V. E. Maryzhihin; I. V. Sirbu (Известия ТИНРО)
Microelements (Pb, Cd, As, Hg, Fe, Cu, Mn, Cr, Ni) are investigated in the tissues of saffron cod Eleginus gracilis caught in the coastal waters of Sakhalin Island in 2020. The samples of weight about 1.0 g were taken from thawed fish, treated with concentrated nitric acid, and mineralized in a microwave oven; the mineralizates were dissolved in distilled water and quantitatively analyzed twice. The microelements distribution in the organs of fish was heterogeneous, but their concentration never exceeded the permissible sanitary and hygienic levels.